1998
DOI: 10.1063/1.368077
|View full text |Cite
|
Sign up to set email alerts
|

Formation of regular step arrays on Si(111)7×7

Abstract: Highly regular arrays of steps are produced on vicinal Si(111)7ϫ7 surfaces. A tilt of the surface normal from ͑111͒ toward ͑1 1 2͒ produces single steps ͑0.3 nm high and typically 15 nm apart͒. The opposite tilt toward ͑1 1 2͒ produces bunched steps with adjustable height ͑1-5 nm͒ and a spacing of 70 nm. Preparation criteria for straight edges and regular spacings are determined, taking into account the miscut angle ͑azimuthal and polar͒, annealing sequence, current direction, and applied stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 32 publications
(42 reference statements)
4
74
0
Order By: Relevance
“…[5][6][7] Steps on Si͑111͒ vicinal surfaces have been decorated by metals, 3,8 semiconductors, 4,9 and organic molecules. 10 The challenge is to improve the homogeneity of the nanowire array and the crystallinity and the aspect ratio of the wires.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Steps on Si͑111͒ vicinal surfaces have been decorated by metals, 3,8 semiconductors, 4,9 and organic molecules. 10 The challenge is to improve the homogeneity of the nanowire array and the crystallinity and the aspect ratio of the wires.…”
mentioning
confidence: 99%
“…[2][3][4] A suitable template is the vicinal surface of a Si͑111͒ single crystal, since the structure of the step train on this surface can be controlled to a large extent. [5][6][7] Steps on Si͑111͒ vicinal surfaces have been decorated by metals, 3,8 semiconductors, 4,9 and organic molecules. 10 The challenge is to improve the homogeneity of the nanowire array and the crystallinity and the aspect ratio of the wires.…”
mentioning
confidence: 99%
“…STM measurements were performed between T = 5.2 − 6.5 K where indicated. Vicinal Si(111) samples (1.1 • miscut toward [112]) utilized were n-doped (Sb) with a resistivity of 0.022 − 0.06 Ω-cm 26 . Pb was deposited on Si(111) − 7 × 7 from a thermal evaporator with typical growth rates of 0.5 ML per minute at room temperature, resulting in flat-top mesas 19,27,28 .…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…16 Himpsel and co-workers have experimentally demonstrated that vicinal Si͑111͒ surfaces can serve as templates for self-assembly of one-dimensional ͑1D͒ nanostructures, 17,18 because a regular array of straight steps can be obtained on these surfaces. [19][20][21] Improving their method of the straight-step preparation by substrate annealing with step-parallel direct current ͑dc͒, we have found that the "kink-up" direction ͑ascending kinks of the steps͒ of the dc is effective to obtain atomically straight step edges ͑on the order of 1 m in length͒ probably due to electromigration of the surface atoms. 22 We have studied the growth behavior of Si ͑Ref.…”
Section: Introductionmentioning
confidence: 99%